El Chino - Say, Allen (Boston : Houghton Mifflin Co., 1990)
A biography of Bill Wong, a Chinese American who became a famous bullfighter in Spain.
Keywords: El Chino -- Juvenile literature; El Chino; El Chino; El Chino; Bullfighters -- United States -- Biography -- Juvenile literature; Bullfighters; JUVENILE NONFICTION / Biography & Autobiography / General; Bullfighters; Bullfighters -- Biography; United States; Local author; Children's nonfiction; Biographies; Biography; Juvenile works; Biographies